1999
DOI: 10.1074/jbc.274.29.20406
|View full text |Cite
|
Sign up to set email alerts
|

Formation of N ε-(Hexanonyl)lysine in Protein Exposed to Lipid Hydroperoxide

Abstract: The objectives of this study were to estimate the structure of the lipid hydroperoxide-modified lysine residue and to prove the presence of the adducts in vivo. The reaction of lipid hydroperoxide toward the lysine moiety was investigated employing N-benzoyl-glycyl-L-lysine (Bz-Gly-Lys) as a model compound of Lys residues in protein and 13-hydroperoxyoctadecadienoic acid (13-HPODE) as a model of the lipid hydroperoxides. One of the products, compound X, was isolated from the reaction mixture of 13-HPODE and Bz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(62 citation statements)
references
References 20 publications
(23 reference statements)
2
58
1
Order By: Relevance
“…In the present study, we evaluated the levels of 8-OHdG [36] and HEL [20], which are both oxidative stress markers, in whole saliva as biomarkers in clinically healthy individuals (Group 1). Both 8-OHdG and HEL decreased significantly after LDOA of CaIFN-4 In Group 1, 4 of 5 dogs tested positive for occult blood, but this rate decreased during LDOA of CaIFN-4 (data not shown), possibly reflecting stress levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we evaluated the levels of 8-OHdG [36] and HEL [20], which are both oxidative stress markers, in whole saliva as biomarkers in clinically healthy individuals (Group 1). Both 8-OHdG and HEL decreased significantly after LDOA of CaIFN-4 In Group 1, 4 of 5 dogs tested positive for occult blood, but this rate decreased during LDOA of CaIFN-4 (data not shown), possibly reflecting stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…The saliva samples of the dogs in Group 1 were centrifuged at 10,000  g for 10 min, and the supernatant was used to determine 8-hydroxydeoxyguanosine (8-OHdG) and N-(Hexanoyl) Lysine (HEL) levels as oxidative stress biomarkers [36,20] with enzyme-linked immunosorbent assay (ELISA) kits (Japan Institute for the Control of Aging, Nikken SEIL Corporation, Fukuroi, Shizuoka, Japan).…”
Section: Determination Of Salivary 8-hydroxydeoxyguanosine and N-(hementioning
confidence: 99%
“…Immunoreactivities for N ⑀ -(hexanonyl)lysine (HEL), 4 4-hydroxynonenal (4-HNE), and 8-hydroxy-2Ј-deoxyguanosine (8-OHdG) in tMCAO models were detected using antibodies against HEL (1:500; MHL-020; JAICA, Shizuoka, Japan), 4-HNE (1:400; MHN-020; JAICA), and 8-OHdG (1:50; MOG-020; JAICA). 5 The numbers of positive cells for each marker in the 3 randomized 0.5 mm 2 areas in the ischemic core were counted.…”
Section: Immunohistochemistry For N ⑀ -(Hexanonyl)lysine 4-hydroxynomentioning
confidence: 99%
“…We have reported that HEL accumulates in animal tissue in which oxidative stress is induced. [7][8][9] In this study, we expected that biomolecules in which proteins and/or aminolipids are modified by lipid decomposition products might be a useful oxidative stress marker in rice damaged oxidatively, as well as in animal tissue. Hence, we investigated whether the reduction in germination ability resulted from oxidative stress during storage of rice at high temperatures, and whether HEL can be used effectively as an oxidative stress biomarker in rice.…”
mentioning
confidence: 99%
“…6,20) We have identified N " -(hexanonyl)-lysine (HEL) as an adduct with an amide bond between the N " -amino group and lipid-derived part. 7) It has reported that the antibody against this adduct was useful as a biomarker of oxidative stress in animal tissue, 8,9) but it had not yet been reported whether HEL accumulates in plant tissue damaged by oxidative stress. As Fig.…”
mentioning
confidence: 99%